Epistemology of the Indonesian Law State (Re-conceptualization of Indonesian Law) (Law Research Review Quarterly, 2016)
The concept of the rule of law in Indonesia has changed after the amendment to the 1945 Constitution. After the amendment, the concept of the rule of law in Indonesia is no longer a rechtsstaat or rule of law, but an Indonesian law state. The purpose of this affirmation has a very important meaning, especially if it is associated with the legal system that already exists in the world. The concept of a legal state rechtsstaat and rule of law is very influential for the Indonesian rule of law. Therefore, the affirmation of the rule of law of Indonesia is not simple given the very strong influence of the existing legal system on Indonesian law from then until now - especially from Europe. The question arises which will contain what Indonesian legal concepts are related to the Indonesian Law State. What is history and development called Indonesian law? To look for Indonesian law that can cover a variety of possible laws in one space, it is important to examine how to conceptualize and need to reconceptualize the law. In legal studies it is important to validly position Indonesia's legal position in the development of legal science.